2009
DOI: 10.1007/s11239-009-0353-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet activation in patients with slow coronary flow

Abstract: We tested the hypothesis that increased platelet activation may be present in patients with slow coronary flow (SCF) and may contribute to the pathogenesis of slow coronary flow phenomenon (SCFP). Fifty patients angiographically proven normal coronary flow (control group; mean age = 61.3 +/- 7.0 years, 43 male) and 50 patients with angiographically proven SCF in all coronary arteries (patient group; man age = 62.7 +/- 6.7 years, 38 male) were included in the present study. Coronary flow rates of all subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
(29 reference statements)
2
23
1
1
Order By: Relevance
“…Among aforementioned etiological causes, enhanced thrombogenicity has been known as another player in SCF pathogenesis. 17 Gokce et al 7 showed that patients with SCF had increased platelet aggregability in the ristocetin groups when compared with the control group. Turkmen et al 18 illustrated that factor XI and XII activities were significantly higher in patients with SCF when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Among aforementioned etiological causes, enhanced thrombogenicity has been known as another player in SCF pathogenesis. 17 Gokce et al 7 showed that patients with SCF had increased platelet aggregability in the ristocetin groups when compared with the control group. Turkmen et al 18 illustrated that factor XI and XII activities were significantly higher in patients with SCF when compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Futhermore, Han et al [23] reported that MPV is a predictive marker for stroke or CAD, and Greisenegger et al [24] determined that an elevated MPV is associated with a poorer outcome for acute ischemic cerebrovascular events independent of other clinical parameters. Previous studies have also reported that high MPV levels are related with cardiovascular risk [25] and that these levels increase in patients with cardiac conditions [26][27][28] who have a poor prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…Clinical investigations have identified that these cohorts of patients have low resting coronary sinus oxygen saturation rates [7] and increased platelet activation [8] compared with control subjects. Basic molecular studies have also identified a range of elevated cardiovascular disease plasma markers such as homocysteine [9], endothelin-1 [10] and soluble adhesion molecules ICAM-1, VCAM-1 and E-selectin [11] in this group of patients.…”
Section: Discussionmentioning
confidence: 99%